Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 12 - National Research Council (The National Academies Press, 2012)
Extremely hazardous substances (EHSs) can be released accidentally as a result of chemical spills, industrial explosions, fires, or accidents involving railroad cars and trucks transporting EHSs. Workers and residents in communities surrounding industrial facilities where EHSs are manufactured, used, or stored and in communities along the nation's railways and highways are potentially at risk of being exposed to airborne EHSs during accidental releases or intentional releases by terrorists. Using the 1993 and 2001 NRC guidelines reports, the National Advisory Committee - consisting of members from the Environmental Protection Agency, the Department of Defense, the Department of Energy, the Department of Transportation, other federal and state governments, the chemical industry, academia, and other organizations form the private sector has developed Acute Exposure Guideline Levels (AEGL) for more than 270 EHSs. In 1998, the EPA and DOD requested that the NRC independently reviewed the AEGLs developed by the NAC. In response to that request, the NRC organized within its Committee on Toxicology the Committee on Acute Exposure Guideline Levels, which prepared this report, Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 12. This report explains the scientifically valid conclusions that are based on the data reviewed by NAC and consistent with the NRC guideline reports and provides comments and recommendations for how AEGL could be improved.
Keywords: Environment and Environmental Studies; Health and Medicine

Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 13 - National Research Council (The National Academies Press, 2012)
At the request of the Department of Defense and the Environmental Protection Agency, the National Research Council has reviewed the relevant scientific literature compiled by an expert panel and established Acute Exposure Guideline Levels (AEGLs) for several chemicals. AEGLs represent exposure levels below which adverse health effects are not likely to occur and are useful in responding to emergencies, such as accidental or intentional chemical releases in community, workplace, transportation, and military settings, and for the remediation of contaminated sites. Three AEGLs are approved for each chemical, representing exposure levels that result in: 1) notable but reversible discomfort; 2) long-lasting health effects; and 3) life-threatening health impacts. Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 13 includes AEGLs for boron trifluoride, bromoacetone, chloroacetone, hexafluoroacetone, perchloryl fluoride, piperidine, propargyl alcohol, trimethoxysilane and tetramethoxysilane, and trimethylbenzenes.
Keywords: Environment and Environmental Studies

Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 9 - National Research Council (The National Academies Press, 2010)
This book is the ninth volume in the series Acute Exposure Guideline Levels for Selected Airborne Chemicals, and reviews AEGLs for bromine, ethylene oxide, furan, hydrogen sulfide, propylene oxide, and xylenes.
Keywords: Environment and Environmental Studies

Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 7 - National Research Council (The National Academies Press, 2009)
This book is the seventh volume in the series Acute Exposure Guideline Levels for Selected Airborne Chemicals, and includes AEGLs for acetone cyanohydrin, carbon disulfide, monochloroacetic acid, and phenol. At the request of the Department of Defense, the National Research Council has reviewed the relevant scientific literature compiled by an expert panel and established Acute Exposure Guideline Levels (AEGLs) for 12 new chemicals. AEGLs represent exposure levels below which adverse health effects are not likely to occur and are useful in responding to emergencies such as accidental or intentional chemical releases in the community, the workplace, transportation, the military, and for the remediation of contaminated sites. Three AEGLs are approved for each chemical, representing exposure levels that result in: 1) notable but reversible discomfort; 2) long-lasting health effects; and 3) life-threatening health impacts.
Keywords: Environment and Environmental Studies

Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 8 - National Research Council (The National Academies Press, 2010)
This book is the eighth volume in the series Acute Exposure Guideline Levels for Selected Airborne Chemicals, and reviews AEGLs for acrolein, carbon monoxide, 1,2-dichloroethene, ethylenimine, fluorine, hydrazine, peracetic acid, propylenimine, and sulfur dioxide for scientific accuracy, completeness, and consistency with the NRC guideline reports.
Keywords: Environment and Environmental Studies; Health and Medicine

Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 2 - National Research Council (The National Academies Press, 2002)
This book reviews toxicity documents on five chemicals that can be released in the air from accidents at chemical plants, storage sites, or during transportation. The documents were prepared by the National Advisory Committee on Acute Exposure Guideline Levels for Hazardous Substances and were evaluated for their scientific validity, comprehensives, internal consistency, and conformance to the 1993 guidelines report.
Keywords: Environment and Environmental Studies; Space and Aeronautics

Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 6 - National Research Council (The National Academies Press, 2008)
This book is the sixth volume in the series Acute Exposure Guideline Levels for Selected Airborne Chemicals, and includes AEGLs for chemicals such as ammonia, nickel carbonyl and phosphine, among others. At the request of the Department of Defense, the National Research Council has reviewed the relevant scientific literature compiled by an expert panel and established Acute Exposure Guideline Levels (AEGLs) for 12 new chemicals. AEGLs represent exposure levels below which adverse health effects are not likely to occur and are useful in responding to emergencies such as accidental or intentional chemical releases in the community, the workplace, transportation, the military, and for the remediation of contaminated sites. Three AEGLs are approved for each chemical, representing exposure levels that result in: 1) notable but reversible discomfort; 2) long-lasting health effects; and 3) life-threatening health impacts.
Keywords: Environment and Environmental Studies; Health and Medicine

Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 18 - National Research Council (The National Academies Press, 2014)
Extremely hazardous substances can be released accidentally as a result of chemical spills, industrial explosions, fires, or accidents involving railroad cars and trucks transporting EHSs. Workers and residents in communities surrounding industrial facilities where these substances are manufactured, used, or stored and in communities along the nation's railways and highways are potentially at risk of being exposed to airborne EHSs during accidental releases or intentional releases by terrorists. Pursuant to the Superfund Amendments and Reauthorization Act of 1986, the U.S. Environmental Protection Agency (EPA) has identified approximately 400 EHSs on the basis of acute lethality data in rodents. Acute Exposure Guideline Levels for Selected Airborne Chemicals, Volume 18 identifies, reviews, and interprets relevant toxicologic and other scientific data for selected AEGL documents for bromine chloride, carbonyl fluoride, selected halogen fluorides, and oxygen difluoride in order to develop acute exposure guideline levels (AEGLs) for these high-priority, acutely toxic chemicals. AEGLs represent threshold exposure limits (exposure levels below which adverse health effects are not likely to occur) for the general public and are applicable to emergency exposures ranging from 10 minutes (min) to 8 h. Three levels - AEGL-1, AEGL-2, and AEGL-3 - are developed for each of five exposure periods (10 min, 30 min, 1 h, 4 h, and 8 h) and are distinguished by varying degrees of severity of toxic effects. This report will inform planning, response, and prevention in the community, the workplace, transportation, the military, and the remediation of Superfund sites.
Keywords: Environment and Environmental Studies

Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 10 - National Research Council (The National Academies Press, 2011)
Extremely hazardous substances (EHSs)&sup2 can be released accidentally as a result of chemical spills, industrial explosions, fires, or accidents involving railroad cars and trucks transporting EHSs. Workers and residents in communities surrounding industrial facilities where EHSs are manufactured, used, or stored and in communities along the nation's railways and highways are potentially at risk of being exposed to airborne EHSs during accidental releases or intentional releases by terrorists. Pursuant to the Superfund Amendments and Reauthorization Act of 1986, the U.S. Environmental Protection Agency (EPA) has identified approximately 400 EHSs on the basis of acute lethality data in rodents. As part of its efforts to develop acute exposure guideline levels for EHSs, EPA and the Agency for Toxic Substances and Disease Registry (ATSDR) in 1991 requested that the National Research Council (NRC) develop guidelines for establishing such levels. In response to that request, the NRC published Guidelines for Developing Community Emergency Exposure Levels for Hazardous Substances in 1993. Subsequently, Standard Operating Procedures for Developing Acute Exposure Guideline Levels for Hazardous Substances was published in 2001, providing updated procedures, methodologies, and other guidelines used by the National Advisory Committee (NAC) on Acute Exposure Guideline Levels for Hazardous Substances and the Committee on Acute Exposure Guideline Levels (AEGLs) in developing the AEGL values. In 1998, EPA and DOD requested that the NRC independently review the AEGLs developed by NAC. In response to that request, the NRC organized within its Committee on Toxicology (COT) the Committee on Acute Exposure Guideline Levels, which prepared this report. Acute Exposure Guideline Levels for Selected Airborne Chemicals is the tenth volume of the series and documents for N,N-dimethylformamide, jet propellant fuels 5 and 8, methyl ethyl ketone, perchloromethyl mercaptan, phosphorus oxychloride, phosphorus trichloride, and sulfuryl chloride.
Keywords: Environment and Environmental Studies

Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 19 - National Research Council (The National Academies Press, 2015)
Extremely hazardous substances can be released accidentally as a result of chemical spills, industrial explosions, fires, or accidents involving railroad cars and trucks transporting EHSs. Workers and residents in communities surrounding industrial facilities where these substances are manufactured, used, or stored and in communities along the nation's railways and highways are potentially at risk of being exposed to airborne EHSs during accidental releases or intentional releases by terrorists. Pursuant to the Superfund Amendments and Reauthorization Act of 1986, the U.S. Environmental Protection Agency (EPA) has identified approximately 400 EHSs on the basis of acute lethality data in rodents. Acute Exposure Guideline Levels for Selected Airborne Chemicals, Volume 19 identifies, reviews, and interprets relevant toxicologic and other scientific data for selected AEGL documents for cyanide salts, diketene, methacrylaldehyde, pentaborane, tellurium hexafluoride, and tetrafluoroethylene in order to develop acute exposure guideline levels (AEGLs) for these high-priority, acutely toxic chemicals. AEGLs represent threshold exposure limits (exposure levels below which adverse health effects are not likely to occur) for the general public and are applicable to emergency exposures ranging from 10 minutes (min) to 8 h. Three levels - AEGL-1, AEGL-2, and AEGL-3 - are developed for each of five exposure periods (10 min, 30 min, 1 h, 4 h, and 8 h) and are distinguished by varying degrees of severity of toxic effects. This report will inform planning, response, and prevention in the community, the workplace, transportation, the military, and the remediation of Superfund sites.
Keywords: Environment and Environmental Studies

Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 15 - National Research Council (The National Academies Press, 2013)
Acute Exposure Guideline Levels for Selected Airborne Chemicals, Volume 15 identifies, reviews, and interprets relevant toxicologic and other scientific data for ethyl mercaptan, methyl mercaptan, phenyl mercaptan, tert-octyl mercaptan, lewisite, methyl isothiocyanate, and selected monoisocyanates in order to develop acute exposure guideline levels (AEGLs) for these high-priority, acutely toxic chemicals. AEGLs represent threshold exposure limits (exposure levels below which adverse health effects are not likely to occur) for the general public and are applicable to emergency exposures ranging from 10 minutes (min) to 8 h. Three level—AEGL-1, AEGL-2, and AEGL-3—are developed for each of five exposure periods (10 min, 30 min, 1 h, 4 h, and 8 h) and are distinguished by varying degrees of severity of toxic effects. This report will inform planning, response, and prevention in the community, the workplace, transportation, the military, and the remediation of Superfund sites.
Keywords: Environment and Environmental Studies

Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 14 - National Research Council (The National Academies Press, 2013)
Extremely hazardous substances (EHSs) can be released accidentally as a result of result of chemical spills, industrial explosions, fires, or accidents involving railroad cars and trucks transporting EHSs. Workers and residents in communities surrounding industrial facilities where EHSs are manufactured, used, or stored and in communities along the nation's railways and highways are potentially at risk of being exposed to airborne EHSs during accidental releases or intentional releases by terrorists. Pursuant to the Superfund Amendments and Reauthorization Act of 1986, the U.S. Environmental Protection Agency (EPA) has identified approximately 400 EHSs on the basis of acute lethality data in rodents. As part of its efforts to develop acute exposure guideline levels for EHSs, EPA and the Agency for Toxic Substances and Disease Registry (ATSDR) in 1991 requested that the National Research Council (NRC) develop guidelines for establishing such levels. In response to that request, the NRC published Guidelines for Developing Community Emergency Exposure Levels for Hazardous Substances in 1993. Subsequently, Standard Operating Procedures for Developing Acute Exposure Guideline Levels for Hazardous Substances was published in 2001, providing updated procedures, methodologies, and other guidelines used by the National Advisory Committee (NAC) on Acute Exposure Guideline Levels for Hazardous Substances and the Committee on Acute Exposure Guideline Levels (AEGLs) in developing the AEGL values. Using the 1993 and 2001 NRC guidelines reports, the NAC—consisting of members from EPA, the Department of Defense (DOD), the Department of Energy (DOE), the Department of Transportation (DOT), other federal and state governments, the chemical industry, academia, and other organizations from the private sector—has developed AEGLs for more than 270 EHSs. In 1998, EPA and DOD requested that the NRC independently review the AEGLs developed by NAC. In response to that request, the NRC organized within its Committee on Toxicology (COT) the Committee on Acute Exposure Guideline Levels, which prepared this report. This report is the fourteenth volume in that series. Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 14 summarizes the committee's conclusions and recommendations.
Keywords: Environment and Environmental Studies

Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 16 - National Research Council (The National Academies Press, 2014)
Extremely hazardous substances can be released accidentally as a result of chemical spills, industrial explosions, fires, or accidents involving railroad cars and trucks transporting EHSs. Workers and residents in communities surrounding industrial facilities where these substances are manufactured, used, or stored and in communities along the nation's railways and highways are potentially at risk of being exposed to airborne extremely hazardous substances during accidental releases or intentional releases by terrorists. Pursuant to the Superfund Amendments and Reauthorization Act of 1986, the U.S. Environmental Protection Agency has identified approximately 400 extremely hazardous substances on the basis of acute lethality data in rodents. Acute Exposure Guideline Levels for Selected Airborne Chemicals, Volume 16 identifies, reviews, and interprets relevant toxicologic and other scientific data for selected aliphatic nitriles, benzonitrile, methacrylonitrile, allyl alcohol, hydrogen selenide, ketene, and tear gasin order to develop acute exposure guideline levels (AEGLs) for these high-priority, acutely toxic chemicals. AEGLs represent threshold exposure limits (exposure levels below which adverse health effects are not likely to occur) for the general public and are applicable to emergency exposures ranging from 10 minutes (min) to 8 h. Three levels - AEGL-1, AEGL-2, and AEGL-3 - are developed for each of five exposure periods (10 min, 30 min, 1 h, 4 h, and 8 h) and are distinguished by varying degrees of severity of toxic effects. This report will inform planning, response, and prevention in the community, the workplace, transportation, the military, and the remediation of Superfund sites.
Keywords: Environment and Environmental Studies

Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 11 - National Research Council (The National Academies Press, 2012)
At the request of the Department of Defense and the Environmental Protection Agency, the National Research Council has reviewed the relevant scientific literature compiled by an expert panel and established Acute Exposure Guideline Levels (AEGLs) for several chemicals. AEGLs represent exposure levels below which adverse health effects are not likely to occur and are useful in responding to emergencies, such as accidental or intentional chemical releases in community, workplace, transportation, and military settings, and for the remediation of contaminated sites. Three AEGLs are approved for each chemical, representing exposure levels that result in: 1) notable but reversible discomfort; 2) long-lasting health effects; and 3) life-threatening health impacts. This volume in the series includes AEGLs for bis-chloromethyl ether, chloromethyl methyl ether, chlorosilanes, nitrogen oxides, and vinyl chloride.
Keywords: Environment and Environmental Studies; Health and Medicine

Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 17 - National Research Council (The National Academies Press, 2014)
Extremely hazardous substances can be released accidentally as a result of chemical spills, industrial explosions, fires, or accidents involving railroad cars and trucks transporting EHSs. Workers and residents in communities surrounding industrial facilities where these substances are manufactured, used, or stored and in communities along the nation's railways and highways are potentially at risk of being exposed to airborne EHSs during accidental releases or intentional releases by terrorists. Pursuant to the Superfund Amendments and Reauthorization Act of 1986, the U.S. Environmental Protection Agency (EPA) has identified approximately 400 EHSs on the basis of acute lethality data in rodents. Acute Exposure Guideline Levels for Selected Airborne Chemicals, Volume 17 identifies, reviews, and interprets relevant toxicologic and other scientific data for selected AEGL documents for acrylonitrile, carbon tetrachloride, cyanogen, epichlorohydrin, ethylene chlorohydrin, toluene, trimethylacetyl chloride, hydrogen bromide, and boron tribromide in order to develop acute exposure guideline levels (AEGLs) for these high-priority, acutely toxic chemicals. AEGLs represent threshold exposure limits (exposure levels below which adverse health effects are not likely to occur) for the general public and are applicable to emergency exposures ranging from 10 minutes (min) to 8 h. Three levels - AEGL-1, AEGL-2, and AEGL-3 - are developed for each of five exposure periods (10 min, 30 min, 1 h, 4 h, and 8 h) and are distinguished by varying degrees of severity of toxic effects. This report will inform planning, response, and prevention in the community, the workplace, transportation, the military, and the remediation of Superfund sites.
Keywords: Environment and Environmental Studies

Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 1 - National Research Council (The National Academies Press, 2000)
In the Bhopal disaster of 1984, approximately 2,000 residents living near a chemical plant were killed and 20,000 more suffered irreversible damage to their eyes and lungs following the accidental release of methyl isocyanate. This tragedy served to focus international attention on the need for governments to identify hazardous substances and assist local communities in planning how to deal with emergency exposures. Since 1986, the U.S. Environmental Protection Agency has been tasked with identifying extremely hazardous substances and, in cooperation with the Federal Emergency Management Agency and the Department of Transportation, assist local emergency response planners. The National Advisory Committee on Acute Exposure Guideline Levels for Hazardous Substances was established in 1995 to develop acute exposure guideline levels (AEGLs) for high priority toxic chemicals that could be released into the air from accidents at chemical plants, storage sites, or during transportation. This book reviews toxicity documents on five chemicals—chlorine, hydrogen chloride, hydrogen fluoride, toluene, and uranium hexafluoride—for their scientific validity, comprehensives, internal consistency, and conformance to the 1993 guidelines report.
Keywords: Environment and Environmental Studies

Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 3 - National Research Council (The National Academies Press, 2003)
This report reviews documents on acute exposure guideline levels (AEGLs) for nerve agents GA (tabun), GB (sarin), GD (soman), GD, and VX, sulfur mustard, diborane, and methyl isocyanate. The documents were developed by the National Advisory Committee on Acute Exposure Guideline Levels for Hazardous Chemicals (NAC). The subcommittee concludes that the AEGLs developed in those documents are scientifically valid conclusions based on data reviewed by NAC and are consistent with the NRC reports on developing acute exposure guideline levels.
Keywords: Environment and Environmental Studies

Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 5 - National Research Council (The National Academies Press, 2007)
In 1993, the National Research Council's Committee on Toxicology developed criteria and methods for EPA and the Agency for Toxic Substances and Disease Registry (ATSDR) to develop community emergency exposure levels for extremely hazardous substances for the general population. A few years later, the National Advisory Committee for Acute Exposure Guideline Levels for Hazardous Substances (NAC)—composed of members of EPA, DOD, other federal and state agencies, industry, academia, and other organizations—was established to identify, review, and interpret toxicologic and other scientific data to develop acute exposure guidelines (AEGLs) for high-priority, acutely toxic chemicals. Three levels—AEGL-1, AEGL-2, and AEGL-3 are developed for each of five exposure periods (10 min, 30 min, 1 hr, 4 hr, and 8 hr) and are distinguished by varying degrees of severity of toxic effects. This current report reviews the NAC reports for their scientific validity, completeness, and consistency with the NRC guideline reports developed in 1993 and 2001. This report is the fifth volume in the series and covers AEGLs for chlorine dioxide, chlorine trifluoride, cyclohexylamine, ethylenediamine, hydrofluoroether-7100, and tetranitromethane. It concludes that the AEGLs developed by NAC are scientifically valid and consistent with the NRC guideline reports. AEGLs are needed for a wide range of planning, response, and prevention applications. These values provide data critical to evacuation decisions and discussions between community leaders and industries as they seek ways to minimize the health impact should the chemical release occur. Some of the finalized AEGLs have been officially adopted by the Department of the Army, FEMA, and the Department of Transportation as the official levels for use by those agencies.
Keywords: Environment and Environmental Studies

Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 4 - National Research Council (The National Academies Press, 2004)
The Bhopal Disaster of 1984 resulted in the death of around 2,000 residents living near chemical plants and irreversible injuries to more than 20,000 other residents. These numbers can be attributed to the community's lack of awareness concerning the chemicals' existence, dangers and effects, and/or how to react in case of emergency. The disaster emphasized the need for governments to identify hazardous substances and to aid local communities in developing plans for emergency exposures. As a result, the United States government issued the Superfund Amendments and Reauthorization Act (SARA) of 1986; requiring the identification of extremely hazardous substances (EHSs) by the Environmental Protection Agency (EPA). EPA was also tasked with assisting Local Emergency Planning Committees (LEPCs) in conducting health-hazard assessments to develop emergency-response plans for sites where EHSs are produced, stored, transported, or used. The EPA identified nearly 400 EHSs in terms of their immediate danger to life and health (IDLH) as their first step in assisting these LEPCs. In 1991 the EPA went on to request that the National Research Council (NRC) Committee on Toxicology (COT) develop criteria and methods for developing emergency exposure levels for EHSs for the general population. The COT, who had published many reports on emergency exposure guidance levels at the time, designated the task to a subcommittee. The subcommittee focused on Guidelines for Developing Community Emergency Exposure Levels for Hazardous Substances. Four years later the National Advisory Committee for Acute Exposure Guideline Levels for Hazardous Substances (NAC) was created with a focus on identifying, reviewing, and interpreting relevant toxicologic and other scientific data and developing acute exposure guideline levels (AEGLs) for high-priority, acutely toxic chemicals. In Acute Exposure Guideline Levels for Selected Airborne Chemicals:Volume 4, the NAC outlines acute exposure guideline levels for chlorine, hydrogen chloride, toluene 2,4, hydrogen fluoride, 2,6-diisocyanate, and uranium hexafluoride.
Keywords: Environment and Environmental Studies